Application Of Self-Management Techniques In Reducing Online Game Addiction Among Rural Teenagers - Wahyuni, Sri; Alimuddin, Nurwahida; Badjarad, Rizqa Sabrina (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2025)
This study aims to determine the effectiveness of applying self-management techniques in reducing online game addiction among adolescents in Tomoli Village, Toribulu District, Parigi Moutong Regency. Theoretically, this study is expected to contribute to the development of science, particularly for students at UIN Datokarama Palu and the Islamic Counseling Department, while practically it will benefit the community, adolescents, and parents in dealing with online game addiction so that adolescents can return to normal life. The study used a quantitative approach with a nonequivalent control group design, involving 10 adolescents with severe addiction levels based on the Game Addiction Scale for Adolescents (GASA). The sample was divided into a control group (5 adolescents without intervention) and an experimental group (5 adolescents with self-management intervention). Data analysis using SPSS version 27 showed a significant difference between the post-test results of the two groups, so it can be concluded that the self-management technique is effective in reducing online game addiction among adolescents in Tomoli Village.